Phase II single-arm study of a combination of obinutuzumab and venetoclax in early relapsed or refractory diffuse large B-cell lymphoma—final results of the AGMT NHL15B study - Jaeger, Ulrich; Simonitsch-Klupp, Ingrid; Klammer, Patrick; Egle, Alexander; Heibl, Sonja; Neumeister, Peter; Willenbacher, Ella; Erlsbacher, Florian; Larcher-Senn, Julian; Staber, Philipp B.; Porpaczy, Edit; Skrabs, Cathrin; et al. (Frontiers in Hematology, 2024)
BackgroundPatients with diffuse large B-cell lymphoma (DLBCL) relapsing early (within 12 months) or primary refractory to induction therapy with rituximab (R) and CHOP have a poor prognosis. We therefore initiated a study with obinutuzumab and venetoclax.Study design and methodsTwenty-one patients with DLBCL (relapsed within 12 months or primary refractory), detectable Bcl-2 protein expression, and CD20 positivity were included in this prospective single-arm study between 2016 and 2021. Obinutuzumab was administered i.v. at a dose of 1,000 mg on days 1, 8, and 15 in cycle 1 and on day 1 of each of the following 21-day cycles. Venetoclax was given at 800 mg daily p.o. continuously. Treatment was repeated for up to three cycles. Eligible patients were planned to either proceed to cellular therapies or receive up to nine cycles of maintenance. The primary endpoint was objective response rate (ORR) after three cycles (Eudract Nr. 2016-001760-10 and NCT02987400).ResultsTwenty-one patients (median age, 64 years) with refractory or early relapsed DLBCL after one (N = 11) to four previous lines of therapy were included. The majority of patients received three cycles of obinutuzumab/venetoclax (range, 1–8). The regimen was well tolerated with manageable cytopenias and infections. Severe adverse events related to treatment were observed in 9.5%. The ORR was 38.1% (8/21 patients) with a best response of five complete remissions (CRs; 23.8%) and three partial remissions (PRs; 14.2%). The primary endpoint (45% ORR) was not met. Response duration was 83.3% at 84 days, with a progression-free survival of 38.8% at 84 days and 25.9% at 168 days and a median overall survival of 169.1 weeks. All deaths were due to underlying disease. Seven patients became eligible for autologous transplant. Overall, nine patients (42.8%) received 11 cellular therapies (5 ASCT and 6 CAR-T). Three patients went directly from obinutuzumab/venetoclax to CAR-T therapy. All patients had successful peripheral stem cell or T-cell harvests. Characteristics of responders include relapsed disease (response rate, 6 of 11 = 54%), very good or good R-IPI (7 of 8), and low number of previous therapies (median = 1).ConclusionObinutuzumab/venetoclax represents an effective chemo-free relapse regimen with low toxicity that can be followed by cellular therapies, particularly CAR-T cells.